CON: Portal Vein Thrombosis Does Not Impact Liver Transplantation Outcomes. Issue 4 (3rd November 2020) - Sherman, Courtney; Syed, Shareef; Gardner, James; Yao, Francis Y.
Abstract : Watch a video presentation of this article Watch an interview with the author